Review of the current and post-Brexit UK legal framework on the regulation of genetic technologies - Firmansyah, Adiba (Bioethica, 2021)
The launch of a nationwide consultation in January 2021 by the UK Department for the Environment, Food and Rural Affairs (Defra) on the regulation of genetic technologies has been used as an opportunity by the UK Government to gauge public and scientific opinion on the applications of gene editing in agriculture and aquaculture. In particular, the consultation sought to consider the controversial question of whether gene editing (GE) should be subject to the same regulations as genetically modified organisms (GMOs). The distinction between GE and GMO products, as well as between the legal regulations governing them, are highly important: currently, the UK still follows the EU’s restrictive approach, whereby gene editing is regulated in the same way as GMOs. However, in light of the UK’s departure from the EU, the UK government seems willing to reconsider this approach and adopt a new regulatory framework characterised by less stringent controls. Accordingly, this review paper examines the current legal framework on gene editing and GMOs in the UK and EU, as well as in other relevant jurisdictions, before then examining the Defra consultation in light of the mixed responses to it from both the scientific community and the general public. The paper concludes with a number of considerations that should inform any proposed post-Brexit reform of the framework that allows for the correct balance to be struck between scientific development, food security, human health, and the environment.